2009
DOI: 10.1021/bm801151r
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis and Allosteric Effects in the HIV-1 Capsid Protein Carboxyl-Terminal Dimerization Domain

Abstract: The carboxyl-terminal domain (CTD, residues 146−231) of the HIV-1 capsid (CA) protein plays an important role in the CA−CA dimerization and viral assembly of the human immunodeficiency virus type 1. Disrupting the native conformation of the CA is essential for blocking viral capsid formation and viral replication. Thus, it is important to identify the exact nature of the structural changes and driving forces of the CTD dimerization that take place in mutant forms. Here, we compare the structural stability, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
(92 reference statements)
1
11
0
Order By: Relevance
“…2(B)], especially at 223 nm, suggesting the possibility of a slight increase in the α‐helical content in the R185W single and double mutant CTDs. Stabilization of the dimerization helix by the R185W mutation is consistent with the overall stabilization of the domain by this mutation, the promiscuous suppression of many lethal mutations by the R185W mutation in vivo ,10 the biophysical,37 and modeling38 studies of the dimerization of HIV‐CTD and the structural studies of Mason‐Pfizer monkey virus particles 4. Although the magnitude of the effect is small, and we cannot be confident that it has biological relevance, it does suggest a possible mechanism of action for the R185W mutation.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…2(B)], especially at 223 nm, suggesting the possibility of a slight increase in the α‐helical content in the R185W single and double mutant CTDs. Stabilization of the dimerization helix by the R185W mutation is consistent with the overall stabilization of the domain by this mutation, the promiscuous suppression of many lethal mutations by the R185W mutation in vivo ,10 the biophysical,37 and modeling38 studies of the dimerization of HIV‐CTD and the structural studies of Mason‐Pfizer monkey virus particles 4. Although the magnitude of the effect is small, and we cannot be confident that it has biological relevance, it does suggest a possible mechanism of action for the R185W mutation.…”
Section: Discussionsupporting
confidence: 65%
“…Multiple mutations in HIV‐CTD in this vicinity had non‐additive effects on dimerization, suggesting that this interface has complicated energetics 39. A computational study of four other mutations in HIV‐CTD suggest that the conformation of the MHR is critical to the correct function of the dimerization interface, even though those residues do not directly participate in the interface 37, 38. These RSV studies are a direct test of that prediction and emphasize the utility of biologically derived suppressors in examining capsid interface surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The CA CTD is smaller than the NTD, and is composed of a short 3 10 helix followed by an extended strand and four α helices (Momany et al, 1996; Gamble et al, 1997, Berthet-Colominas et al, 1999; Worthylake et al, 1999; Alcaraz et al, 2007; Wong et al, 2008; Pornillos et al, 2009; Byeon et al, 2009). The CTD comprises the dimerization interface, which relies on amino acid residues W184 and M185 (Gamble et al, 1997, Alcaraz et al, 2008; Byeon et al, 2009; Yu et al, 2009). Interestingly, Bharat et al (Bharat et al, 2012) recently reported that significant rotations and translations of the two CA domains occur during the maturation process of the Mason–Pfizer monkey retrovirus.…”
Section: Introductionmentioning
confidence: 99%
“…The CA CTD is smaller than the NTD and is composed of a short 3 10 helix followed by an extended strand and four α-helices (Momany et al, 1996; Gamble et al, 1997, Berthet-Colominas et al, 1999; Worthylake et al, 1999; Alcaraz et al, 2007; Wong et al, 2008; Pornillos et al, 2009; Byeon et al, 2009). The CTD appears to have the capacity to dimerize in several ways (Gamble et al, 1997; Worthylake et al, 1999; Ternois et al, 2005; Ivanov et al, 2007; Byeon et al, 2009), and the dimerization interface depends on residues W184 and M185 (Gamble et al, 1997, Alcaraz et al, 2008; Byeon et al, 2009; Yu et al, 2009). Recent evidence suggests that an interface formed by the CTD dimers of three neighboring CA hexamers might be involved in organizing intermolecular contacts of mature HIV-1 cores (Byeon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%